Penerapan Metode Contextual Teaching Learning (CTL) dan E-Learning dalam Perspektif Islam - Abd Madjid (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article will discuss the Islamic perspective to explain the application of contextual teaching learning (CTL) methods found in the Qur'an, by utilizing e-learning that can facilitate online learning. The purpose of this article is to explain the concept of contextual teaching learning (CTL) contained in the verses of the Qur'an and the use of e-learning to improve student learning outcomes in online learning. The method used in writing this article is qualitative research with the type of literature review. The results of this article show that the contextual teaching learning (CTL) method is one method to improve student learning outcomes by learning independently, creatively, student-centered and more meaningful and utilizing e-learning to facilitate learning outcomes in online learning.